The importance of zakat funds for poverty alleviation through ‘Asnaf Entrepreneurship Development Programme in Selangor - Hamdan, Hamdino; Othman, Pazim @ Fadzim; Ahmad, Khaliq (2013)
Islamic Microfinance Program (IMP) through the utilization of zakat fund has been a significant source of capital for entrepreneurship activities among the poor Muslim’s families in Malaysia. Starting from the New Economic Plan (NEP) in 1971, the Malaysian Government has realized the importance of IMP in supporting the microenterprises activities for the purpose of poverty alleviation strategy. ‘Asnaf Entrepreneurs Development Programme’ (AEDP) conducted by Lembaga Zakat Selangor (LZS) is among the pioneers and most established IMPs being introduced in the country. However, there may be doubts whether this programme has achieved its objective of increasing the socio-economic level of the poor. Therefore, the focus of this study is to evaluate the implementation effectiveness of AEDP in increasing the participants’ income for the purpose of poverty alleviation through entrepreneurial concept by conducting microenterprise. The results show that the programme’s processes and procedures, officer’s qualifications, attitudes and experiences affected the participants’ business revenues.